Effect of a pleasure-oriented intervention on the nutritional quality of midafternoon snacks and on the relationship between food liking and perceived healthiness within mother-child dyads. (September 2020) - Poquet, Delphine; Ginon, Emilie; Sénécal, Coraline; Chabanet, Claire; Marette, Stéphan; Issanchou, Sylvie; Monnery-Patris, Sandrine
Highlights: A pleasure-centred intervention was developed to improve the pleasure to consume healthy foods. The relationship between liking and perceived healthiness increased after the intervention. Liking for two unhealthy foods decreased for children in the intervention group. A highly attractive unhealthy food is chosen anyway. Some efforts should be made to regulate advertising of unhealthy foods for children. Abstract: The aims of the present study are to assess the impact of a pleasure-oriented intervention on the nutritional quality of midafternoon snacks chosen by mother-child dyads and to evaluate the evolution of the relationship between the liking and perceived healthiness of the food items offered for the snack choices. Data were collected at two laboratory sessions (T1 and T2), during which children and mothers were separately asked to choose two food items (among 10) for a midafternoon snack, first for themselves and then for the other dyad member. Participants also rated their liking and perceived healthiness of the 10 food items. After T1, dyads were randomly assigned to an experimental group (N = 94) with an in-home pleasure-oriented intervention to stimulate the pleasure of consuming healthy foods or to a control group (N = 93). Our study shows the lack of a significant effect of the intervention on the nutritional quality of snacks chosen at T2. However, for the children in the experimental group, the relationship between liking and perceived healthiness which was not significant at T1 (τmedian = −0.05, P = 0.56) became significant and positive at T2 (τmedian = 0.13, P = 0.002). Moreover, this increase of the relationship in T2 was significantly higher for the experimental group compared to the control group (P = 0.05). For mothers, the existing relationship between liking and perceived healthiness at T1 (τmedian = 0.27, P < 0.001) increased significantly between T1 and T2 (P = 0.006) only in the experimental group, even if this increase was not significantly higher compared to the control group (P = 0.21). Since the relationship between food liking and perceived healthiness in mother-child dyads increased after the intervention, one could argue that this higher positive attitude towards healthy foods could constitute the first step in a behavioural change in favour of healthier choices.